CONTRIBUTION OF PLANNING LEARNING AND TEACHING SKILLS AGAINST PAI LEARNING OUTCOMES OF STATE JUNIOR HIGH SCHOOL STUDENTS IN MEDAN CITY - Neti Eliyati (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2019)
The purpose of this study was to determine the contribution of: (1)planning learning towards PAI learning outcomes of SMP Negeri studentsin Medan City, (2) teaching skills towards PAI learning outcomes of SMPNegeri students in Medan City, and (3) planning learning and teachingskills independently together with the PAI learning outcomes of SMPNegeri students in Medan City. This research was conducted at the StateJunior High School in Medan, North Sumatra Province. The population inthis study were all PAI teachers who taught at the State Junior HighSchool in Medan totaling 105 people with a sample of 82 teachers. Theinstrument for collecting data is the questionnaire. Data analysistechniques are correlation and regression analysis. The research findingsindicate: (1) (1) planning learning towards PAI learning outcomes of SMPNegeri students in Medan City, (2) teaching skills towards PAI learningoutcomes of SMP Negeri students in Medan City, and (3) planninglearning and teaching skills together of the PAI learning outcomes of StateJunior High School students in Medan City.